Invasive alien plants along roadsides in Europe. (13th June 2018) - Follak, S.; Eberius, M.; Essl, F.; Fürdös, A.; Sedlacek, N.; Trognitz, F.
Abstract : This study presents a list of invasive alien plants that are found along roadsides in seven selected European countries – Austria, Germany, the Netherlands, Ireland, Norway, Slovenia and Sweden – and an overview on the role of roadsides as a habitat for invasive alien plants. This compilation is based on national lists of invasive alien plants, a literature search and expert consultation. Comprising 89 species from 31 plant families, species introduced for horticulture dominate the list (65%). Thirteen species (14%) are widespread (occur in four or more countries) and include well‐known invasive plants such as Fallopia japonica, Heracleum mantegazzianum, Solidago canadensis and Solidago gigantea . Seventeen species are listed either on the EPPO List of Invasive Alien Plants or on the EPPO A2 List of pests recommended for regulation as quarantine pests. Five species are on the List of Invasive Alien Species of Union Concern (EU Regulation 1143/2014). The compiled list provides a snap‐shot of invasive alien plants currently found along roadsides in the selected countries. It allows for a more targeted approach to monitoring, containment and control of the most problematic invasive alien plants identified in each country. Moreover, the list may also be used to identify emerging (potentially) invasive alien plants along roadsides in other European countries that warrant monitoring and/or management.